Deforestation and Applicable Related Act in India - S. Kanthimathinathan (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 1, 2022)
Forests are a valuable natural gift to man, or rather to living beings. Forests, which include trees, shrubs, herbs, grass, and other plants, have a climate-moderating effect because they help to maintain ecological balance. They balance the climate, increase soil fertility, prevent soil erosion, and promote perennial stream flow in rain-fed rivers. They provide sanctuary for wild animals, preserve gene pools, and protect tribal people. The trees in the forest draw water from the earth’s bowls and release it into the atmosphere via transpiration, which is returned to the atmosphere via condensation of clouds formed from atmospheric moisture. As a result, forests aid in the completion of the cycle. These are in charge of purifying the air by releasing oxygen into the atmosphere via the photosynthesis process. As a result, it is correct to state that there is a balance between earth, air, water, soil, and plant. Forests hold up the mountains, cushion the rains and they discipline the rivers and control the floods. They are beneficial both directly and indirectly. They directly supply wood, timber, fuel, medicines, and fruits with commercial and industrial value such as news, print, rayon, bidi leaves, gums, resins, charcoal, and so on. They also provide people with work. Forests indirectly preserve the physical features of land, prevent soil erosion, mitigate floods, help streams flow perennially, and thus aid agriculture. The most important effect that forests have on our environment is that they protect it through green and leafy vegetation and wildlife. To protect the environment, it is critical to manage the preservation of forests from deforestation. During the last century, forests have been cut at rates unequalled in the world and they are disappearing at an alarming rate. According to some estimates, India’s vegetation covers over 19% of the country’s total geographical area, well above the recommended 33% and over 40% globally. Thus, there is substantially less vegetative cover than is necessary. The debate above clearly shows that Indians had a culture of guarding and maintaining the forests, and that it was the duty of both the people and the rulers to do so. India also had a culture of worshiping nature in all its glory.